Gentiopicroside-Induced gastric cancer necroptosis via the HIF-1 signaling pathway: A study involving molecular docking and experimental validation. - Bo Xiong; Mingjie Fan; Zhihui Wang; Xiaolu Yang; Shan Cao; Jie Shen; Beibei Fan (PLoS ONE)
Objectives Gentiopicroside is an effective treatment for several types of cancer, inducing numerous forms of programmed cancer cell death. However, there are few investigations into the role of necroptosis. By utilizing molecular docking, and experimental validation, this study aims to investigate whether gentiopicroside elicits necroptosis in gastric cancer. Methods Using software PyMOL and AutoDock, gentiopicroside was docked with RIPK1, RIPK3, MLKL and HIF-1α proteins. And a cell study was performed based on SGC7901 cells. The necroptosis-related proteins and HIF-1 signaling pathways were explored using western blot (WB) analysis. Finally, an animal study was performed to test the inhibitory effect in vivo. Results Docking studies indicated that the docking energies of gentiopicroside to necroptosis-related proteins and necroptosis-characteristic proteins are all below -5 kcal/mol. Additionally, gentiopicroside cells reduce gastric cancer viability and inhibit proliferation. Results from the animal experiments indicated that gentiopicroside inhibits the growth of the gastric cancer xenograft tumor. Western blot and immunohistochemistry (IHC) staining demonstrated that gentiopicroside higher p-receptor-interacting protein kinase 3(p-RIPK3) levels in vitro and in vivo. Conclusion The findings of this study revealed that necroptosis is involved in the inhibitory effect of gentiopicroside toward gastric cancer.